Converting to DFSMSrmm from TLMS - Lovelace, Mary (IBM redbooks, 2004)
DFSMSrmm is the IBM tape management system for OS/390 and z/OS platforms. As part of DFSMS, DFSMSrmm is completely integrated into the IBM storage management strategy. This allows easier installation and maintenance, as well as standard interfaces with other systems components, such as DFSMSdfp and DFSMShsm. DFSMSrmm provides a simple and flexible tape management environment, with support for all tape technologies, including IBM automated tape libraries, manual tapes, and other tape libraries. This IBM Redbooks publication is written for people who are planning to convert from TLMS to DFSMSrmm. We have designed this book to help you with all aspects of the conversion, from the early planning stage through implementation and customization of DFSMSrmm into your production system. We provide details on the differences between DFSMSrmm and TLMS and compare the terminology, data, and functions. We explain how to use the IBM-supplied sample conversion programs and get the converted data validated and ready for use in a production environment. Working samples that are ready for use are included.